Unique Properties of the Rabbit Prion Protein Oligomer. - Ziyao Yu; Pei Huang; Yuanhui Yu; Zhen Zheng; Zicheng Huang; Chenyun Guo; Donghai Lin (PLoS ONE, 2016)
Prion diseases, also known as transmissible spongiform encephalopathies (TSEs), are a group of fatal neurodegenerative disorders infecting both humans and animals. Recent works have demonstrated that the soluble prion protein oligomer (PrPO), the intermediate of the conformational transformation from the host-derived cellular form (PrPC) to the disease-associated Scrapie form (PrPSc), exerts the major neurotoxicity in vitro and in vivo. Rabbits show strong resistance to TSEs, the underlying mechanism is unclear to date. It is expected that the relative TSEs-resistance of rabbits is closely associated with the unique properties of rabbit prion protein oligomer which remain to be addressed in detail. In the present work, we prepared rabbit prion protein oligomer (recRaPrPO) and human prion protein oligomer (recHuPrPO) under varied conditions, analyzed the effects of pH, NaCl concentration and incubation temperature on the oligomerization, and compared the properties of recRaPrPO and recHuPrPO. We found that several factors facilitated the formation of prion protein oligomers, including low pH, high NaCl concentration, high incubation temperature and low conformational stability of monomeric prion protein. RecRaPrPO was formed more slowly than recHuPrPO at physiological-like conditions (< 57°C, < 150 mM NaCl). Furthermore, recRaPrPO possessed higher susceptibility to proteinase K and lower cytotoxicity in vitro than recHuPrPO. These unique properties of recRaPrPO might substantially contribute to the TSEs-resistance of rabbits. Our work sheds light on the oligomerization of prion proteins and is of benefit to mechanistic understanding of TSEs-resistance of rabbits.